Trapezius Perforator Flaps Based on Superficial Cervical Artery and Dorsal Scapular Artery: An Anatomical Study and a Systematic Review of Their Clinical Application. Issue 4 (20th April 2022) - Wang, Qianwen; Li, Zhiqiang; Xu, Xiaohuan; Zhou, Xu; Wang, Tailing
Abstract : Background: The flaps in the trapezius region are routinely elevated as musculocutaneous flaps. The anatomy of trapezius perforators and their clinical application are unclear. Methods: The number and distribution of superficial cervical artery perforators (SCAPs) and dorsal scapular artery perforators (DSAPs) were studied on 8 cadavers. The clinical usage of SCAP and DSAP flaps was investigated through a systematic literature review. Results: A total of 27 SCAPs and 28 DSAPs were found in the 16 hemibacks. The mean calibers of SCAP and DSAP were 0.9 ± 0.2 and 0.8 ± 0.2 mm, respectively. The vascular length to the takeoff of the source artery was 7.3 ± 2.0 cm (range, 4.7–9.7 cm) for SCAPs and was 8.1 ± 2.8 cm (range, 3.2–13.6 cm) for DSAPs. Contour and density heat maps showed that the SCAPs were clustered within approximately 3 to 5 cm above the horizontal line through the medial point of the scapular spine (x-axis) and 5 to 8 cm from the midline (y-axis, P = 0.001) and clustered DSAPs located in approximately 4 to 9 cm below the x-axis and 4 to 10 cm from the y-axis ( P = 0.002). Four SCAP and 19 DSAP flaps were found in literature. The mean sizes of SCAP flaps and DSAP flaps were 18.5 × 7.8 and 16.5 × 8.7 cm, respectively. Conclusions: Both SCAP and DSAP flaps can be elevated with a relatively long pedicle. The anatomical knowledge of the location of major clusters of perforators contributes to the application of these flaps.